Line managers' HR implementation level and work performance: Estimating the mediating role of employee outcomes - Shahid Mahmood; Faisal Qadeer; Muhammad Sheeraz; Kanwal Iqbal Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The ongoing debate to unlock the black box between HRM and performance is yet to be fully concluded. This paper addresses the recent calls by adding three employee outcomes (affective commitment, job satisfaction, and turnover intention) as a mediating mechanism in the causal chain from HR implementation level - i.e., the extent of organization's HR practices that are implemented by each line manager - to work performance. Primary data was collected through a self-administrative survey from 200 permanent employees and 82 supervisors/line managers working in four manufacturing firms. The data was analyzed using SPSS process macros and AMOS. The results reveal that line managers HR implementation level increases work unit performance. Furthermore, an elevated level of HR implementation enhances employees' affective commitment and job satisfaction and reduces their turnover intention and mediating role of these employee outcomes is fully supported by our data. The paper advances the strategic HRM research and contributes by providing a new mechanism to unravel the complexity of HRM-performance linkage debate.
Keywords: 330; HR implementation level; affective commitment; employee outcomes; social exchange theory